Cyperus iria weed growth, survival, and fecundity in response to varying weed emergence times and densities in dry-seeded rice systems - Awan, Tahir Hussain; Ali, Hafiz Haider; Chauhan, Bhagirath Singh (MDPI, 2022)
Cyperus iria is amongst the most threatening weeds of rice in Sri Lanka, India, Pakistan, and the Philippines. Broad knowledge about the ecology and fecundity of C. iria is important for its effective management. Field studies were conducted over two seasons (wet (WS) and dry seasons (DS)) to investigate the influence of C. iria populations (40 and 80 plants m−2) on its growth, survival, and fertility, with four emergence times, 3, 15, 30, and 45 d after rice emergence (DARE), during 2013. We postulated that (a) higher plant density of this weed would result in more biomass production and viable seeds per unit area, (b) interference of rice would reduce the biomass production and fecundity of this weed, and (c) delaying weed emergence would lead to downsizing of its percent survival and seed bank enrichment in soil. The results indicated that rice interference decreased C. iria growth and seed production as compared with those of plants established without rice interference. A linear decrease in the percent survival of C. iria without rice and a sigmoid decrease with rice were observed during both seasons. Plant height of C. iria was moderately affected up to 30 DARE, and a significant reduction was observed at 45 DARE. There was a linear relationship between C. iria shoot dry weight and seed number plant −1, across-weed density, seeding rate of rice, and emergence time. C. iria seed production, 1000-seed weight, and seed yield were greater when seedlings emerged simultaneously with the rice crop (3 DARE) than when they emerged late. Under rice weed interference growth, the production of viable seeds was completely stopped at 45 DARE. The delay in the emergence of C. iria up to 45 DARE was unable to produce seed in both seasons. The results of the current studies advocate that the emergence, weed biomass, and seed production of C. iria can be checked by adopting suitable cultural weed management practices, which can impede the emergence of weed relative to rice. These practices, enabling the respective crops to be more competitive, will foster integrated weed management approaches, thus offering a key role in seed detection to the soil seed reservoir or pool by notorious weeds in the field.